Measuring the angular momentum of a neutron using Earth's rotation - Niels Geerits; Stephan Sponar; Kyle E. Steffen; William M. Snow; Steven R. Parnell; Giacomo Mauri; Gregory N. Smith; Robert M. Dalgliesh; Victor de Haan (Physical Review Research)
A coupling between Earth's rotation and orbital angular momentum (OAM), known as the Sagnac effect, is observed in entangled neutrons produced using a spin-echo interferometer. After correction for instrument systematics the measured coupling is within 5% of theory, with an uncertainty of 7.2%. The OAM in our setup is transverse to the propagation direction and scales linearly with neutron wavelength (4–12.75 Å), so the Sagnac coupling can be varied without mechanically rotating the device, which avoids systematic errors present in previous experiments. The detected transverse OAM of our beam corresponds to 4098±295ℏÅ^{−1},10^{5} times lower than in the previous neutron experiments. This demonstrates the feasibility of using the Sagnac effect to definitively measure neutron OAM and paves the way towards a future observation of the quantum Sagnac effect.